2021
DOI: 10.1542/peds.2021-051155
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal Outcomes for Multisystem Inflammatory Syndrome in Children

Abstract: BACKGROUND In spring 2020, a novel hyperinflammatory process associated with severe acute respiratory syndrome coronavirus 2 multisystem inflammatory syndrome in children (MIS-C) was described. The long-term impact remains unknown. We report longitudinal outcomes from a New York interdisciplinary follow-up program. METHODS All children <21 years of age, admitted to NewYork-Presbyterian with MIS-C in 2020, were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 33 publications
9
98
1
Order By: Relevance
“…All patients showed signs suggesting normal coronary arteries (all score‐ z ≥2.5) (Farooqi et al, 2021) by standard echocardiogram at post‐discharge, except for one patient (P4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients showed signs suggesting normal coronary arteries (all score‐ z ≥2.5) (Farooqi et al, 2021) by standard echocardiogram at post‐discharge, except for one patient (P4).…”
Section: Resultsmentioning
confidence: 99%
“…Standard transthoracic echocardiography was performed according to the recommendations of the American Society of Echocardiography (Farooqi et al, 2021). Cardiac chamber dimensions were obtained using two‐dimensional mode and left ventricle ejection fraction (LVEF) was calculated by Simpson's method (normal LV EF ≥55%) (Farooqi et al, 2021). The z ‐score values of cardiac chambers were calculated according to Lopez et al (normal values between 2 and < +2.5).…”
Section: Methodsmentioning
confidence: 99%
“…Systemic inflammation has been shown to rapidly improve with appropriate treatment, including two studies of 46 and 45 MIS-C patients showing normalization of C-reactive protein, platelet count, liver enzyme levels, albumin levels, and d-dimer levels in the vast majority by 4-6 months, and in some by as early as 6 weeks [65,66]. Cardiac function abnormalities have been shown to improve in a similar manner.…”
Section: Prognosis and Outcomesmentioning
confidence: 93%
“…Coronary artery dilatation (z > 2) has been reported in 9-24.1% of MIS-C cases [11, 12, 13•, 14]. However, in multiple follow-up studies, coronary changes have been shown to resolve with appropriate treatment-one study reported 7 out of 45 (15.6%) patients with coronary changes on admission, all resolved within 1-4 weeks [66], and another study demonstrated coronary changes in 12 out of 50 (24%) patients that resolved by 8 weeks…”
Section: Prognosis and Outcomesmentioning
confidence: 99%
“…Multisystem in ammatory syndrome in children (MIS-C) is a hyperin ammatory response that commonly develops within 2-6 weeks following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, requiring hospitalization in the acute phase (8). While multiple cohorts have shown that MIS-C patients may present with heterogenous signs that include hemodynamic instability, tachycardia, left ventricular dysfunction, and respiratory distress, possibly primary or caused by cardiac dysfunction, (7,13) the pathophysiology of MIS-C and its natural course are yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%